An Equal Burden The Men of the Royal Army Medical Corps in the First World War - Meyer, Jessica (Oxford University Press, 2019)
"An Equal Burden forms the first scholarly study of the Army Medical Services in the First World War to focus on the roles and experiences of the men of the ranks of the Royal Army Medical Corps (RAMC). These men, through their work as stretcher bearers and orderlies, provided a range of labour, both physical and emotional, in aid of the sick and wounded. They were not professional medical caregivers, yet were called upon to provide medical care, however rudimentary; they served in uniform, under military discipline, yet were forbidden, as non-combatants, from carrying weapons. Their service as men in wartime, was thus unique. Structured both chronologically and thematically, this study examines both the work that RAMC rankers undertook and its importance to the running of the chain of medical evacuation. It additionally explores the gendered status of these men within the medical, military and cultural hierarchies of a society engaged in total war, locating their service within the context of that of doctors, female nurses and combatant servicemen. Through close readings of official documents, personal papers, and cultural representations, both verbal and visual, it argues that the ranks of the RAMC formed a space in which non-commissioned servicemen, through their many roles, defined and redefined medical caregiving as men's work in wartime."